2011
DOI: 10.1021/es1037035
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Relative Roles of Ammonia Oxidizing and Heterotrophic Bacteria during the Biotransformation of 17α-Ethinylestradiol and Trimethoprim

Abstract: The biological fate of 17α-ethinylestradiol (EE2; 500 ng/L to 1 mg/L) and trimethoprim (TMP; 1 μg/L to 1 mg/L) was evaluated with flow through reactors containing an ammonia oxidizing bacterial (AOB) culture, two enriched heterotrophic cultures devoid of nitrifier activity, and nitrifying activated sludge (NAS) cultures. AOBs biotransformed EE2 but not TMP, whereas heterotrophs mineralized EE2, biotransformed TMP, and mineralized EE2-derived metabolites generated by AOBs. Kinetic bioassays showed that AOBs bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
106
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(121 citation statements)
references
References 37 publications
12
106
0
2
Order By: Relevance
“…For example, Khunjar et al . (2011) found that both ammonia oxidizing bacteria (AOB) and heterotrophs were capable of catalysing the hydroxylation of EE2, likely using a monooxygenase enzyme, but AOB perform the process more rapidly than heterotrophs. Thus, understanding ‘who’ is performing the function may be more important than the expression of the relevant functional gene to understand what controls a biotransformation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Khunjar et al . (2011) found that both ammonia oxidizing bacteria (AOB) and heterotrophs were capable of catalysing the hydroxylation of EE2, likely using a monooxygenase enzyme, but AOB perform the process more rapidly than heterotrophs. Thus, understanding ‘who’ is performing the function may be more important than the expression of the relevant functional gene to understand what controls a biotransformation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Genes catalysing more specific initial transformations were associated with the transformation of individual compounds. For example, the gene encoding for subunit C of the ammonia monooxygenase gene was associated with EE2 biotransformation (Benjamini–Hochberg adjusted P  =   0.025, ρ = 0.69, adjusted for multiple comparisons), as we would expect given our knowledge of the transformation pathway (Khunjar et al ., 2011). In addition, genes encoding amidase enzymes were associated with atenolol transformation (Helbling et al ., 2010) (Benjamini–Hochberg adjusted P  <   0.03, ρ > 0.78).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic treatment generally results to high biodegradation of TrOC through the action of heterotrophic bacteria and autotrophic ammonia-oxidizing organisms (AOO) in the form of bacteria and archaea [11]. Using 17α-ethinylestradiol as a model pollutant, several research groups have showed that heterotrophs and AOO utilise the enzymes catechol dioxygenase [55] and ammonia monoxygenase [16] for TrOC degradation, respectively. AOO is necessary for the biodegradation of some pharmaceuticals (e.g.…”
Section: Troc Biodegradationmentioning
confidence: 99%
“…AOO is necessary for the biodegradation of some pharmaceuticals (e.g. roxithromycin, erythromycin, and iopromide) [13,17,56], although cooperative biodegradation of 17α-ethinylestradiol, trimethoprim, and their metabolites by heterotrophs and AOO has been observed [55].…”
Section: Troc Biodegradationmentioning
confidence: 99%
“…Therefore, compared with AOB, AOA could be easier to accompany with nitrogen and sulfide removal [23][24]. Furthermore, it has been found that the biotransformation of micropollutants were involved with the cometabolism of ammonia-oxidizing microorganisms [25].…”
mentioning
confidence: 99%